The first assessment of marine debris in a Site of Community Importance in the north-western Adriatic Sea (Mediterranean Sea). Issue 2 (30th January 2017) - Melli, Valentina; Angiolillo, Michela; Ronchi, Francesca; Canese, Simonepietro; Giovanardi, Otello; Querin, Stefano; Fortibuoni, Tomaso
Abstract: At present, few studies have investigated the marine litter abundance, composition and distribution on rocky bottoms due to sampling constraints. We surveyed by means of the ROV imaging technique a system of biogenic rocky outcrops classified as a Site of Community Importance in the Adriatic Sea. A mean density of 3.3 (± 1.8) items/100 m 2 was recorded, with a strong dominance of fishing- and aquaculture-related debris, accounting for 69.4% and 18.9% of the total, respectively. The abundance of litter over the rocky bottoms was significantly higher than that on soft substrates, and its spatial distribution proved to be related to hydrographic factors. Litter-fauna interactions were high, with most of the debris (65.7%) entangling or covering benthic organisms, in particular habitat constructors such as the endangered sea sponge Geodia cydonium . Unless appropriate measures are undertaken to address this problem, the abundance of marine litter in the area is likely to increase. Highlights: The first data on marine litter on rocky bottoms in the Adriatic Sea are presented. The Site of Community Importance " Tegnúe of Chioggia" was shown to be heavily polluted. Fishery and aquaculture (mussel farms) represented the marine debris' main sources. ROV proved to be an effective tool to monitor marine litter in a protected area. The interaction of the marine debris and benthic fauna was assessed.